LSP teacher training and development needs and an online LSP teacher development course - Kereković, Snježana; Breka, Olinka; Bošnjak Terzić, Brankica (Glottodidactica, 2025)
This paper aims to present the European project “Language for Specific Purposes (LSP) Teacher Education Online Course for Professional Development” (LSP-TEOC.Pro) which addresses the need for online LSP teacher development courses to be provided by higher education institutions. The project’s objective was to equip future and early-career LSP teachers with a multilingual online course designed to build essential competencies and skills for effective foreign language instruction in specific contexts. The project was conducted over three years (2020–2023) and completed in seven stages plus evaluation. The paper focuses on the findings from the project’s first stage, which examined existing online LSP teacher training and development programmes across six European countries. Through a structured methodological approach, the paper gathers relevant information about such programmes, revealing a scarcity of specialised online training and development programmes for LSP teachers. These results underscored the pressing need for an innovative, accessible online course for LSP teacher education, which ultimately became the primary outcome of the project.